2021
DOI: 10.1007/s42161-021-00830-4
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and distribution of Sweetpotato viruses and their implication on sweetpotato seed system in Malawi

Abstract: A survey was carried out in 19 districts to investigate the prevalence and distribution of sweetpotato virus disease (SPVD) and its implication on the sustainability of clean seed system in Malawi. A total of 166 leaf samples were collected and tested for the presence of 8 viruses using nitrocellulose membrane enzyme-linked immunosorbent assay (NCM-ELISA). SPVD foliar symptoms were observed in 68.42% of the surveyed districts. There were significant variations in disease incidence and severity (p < 0.001) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Detailed studies have determined the incidence and distribution of sweetpotato viruses in several countries (Abad et al, 2007;Kwak et al, 2007;Mbewe et al, 2021;Sivaprasad & Gubba, 2013). According to Clark et al (2012), the identified viruses have been assigned to nine families as follows: Bromoviridae (1 virus), Bunyaviridae (1), Caulimoviridae (3), Closteroviridae (1), Comoviridae (1), Flexiviridae (1), Geminiviridae (15), Luteoviridae (1), and Potyviridae (9) (Table 4).…”
Section: Sweetpotato Diseases and Virus Complex Affecting Sweetpotatoesmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed studies have determined the incidence and distribution of sweetpotato viruses in several countries (Abad et al, 2007;Kwak et al, 2007;Mbewe et al, 2021;Sivaprasad & Gubba, 2013). According to Clark et al (2012), the identified viruses have been assigned to nine families as follows: Bromoviridae (1 virus), Bunyaviridae (1), Caulimoviridae (3), Closteroviridae (1), Comoviridae (1), Flexiviridae (1), Geminiviridae (15), Luteoviridae (1), and Potyviridae (9) (Table 4).…”
Section: Sweetpotato Diseases and Virus Complex Affecting Sweetpotatoesmentioning
confidence: 99%
“…Detailed studies have determined the incidence and distribution of sweetpotato viruses in several countries (Abad et al., 2007; Kwak et al., 2007; Mbewe et al., 2021; Sivaprasad & Gubba, 2013). According to Clark et al.…”
Section: Pest and Disease Management In Sweetpotato Productionmentioning
confidence: 99%
“…Recycled and locally sourced seed are often heavily infested with pests and diseases ( Mbewe et al, 2021 ). Planting diseased low-quality seed can result in high yield penalties and welfare-reducing effects in developing-country agriculture ( Mann and Warner, 2017 , Okello et al, 2017 , Wossen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…These hindrances prevail both in the field and post-harvest (Abrham et al, 2021;Ngailo et al, 2013;Fuglie, 2007). Among the diseases, SPVD has been reported as the most important sweet potato disease in most of the tropical regions in Africa, and perhaps across the globe (Mbewe et al, 2021;Mukasa et al, 2006). SPVD can cause over 90 % yield loss (in terms of both root and foliage) among susceptible genotypes if not managed (Jones, 2021;Ngailo et al, 2013;Gutierrez et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…SPVD can cause over 90 % yield loss (in terms of both root and foliage) among susceptible genotypes if not managed (Jones, 2021;Ngailo et al, 2013;Gutierrez et al, 2003). SPVD is caused by a dual infection and synergistic relationship between sweet potato feathery mottle potyvirus (SPFMV) and sweet potato chlorotic stunt crinivirus (SPCSV) (Mbewe et al, 2021;Mukasa et al, 2006;Karyeija et al, 2000). SPFMV is a member of potyviridae family.…”
Section: Introductionmentioning
confidence: 99%